A Preliminary Analysis of the Basic Principle and Research Value of Mud Volcano Formation - Wu, Yuanya (International Journal of Natural Resources and Environmental Studies, 2024)
The global plastic usage and production issue during the COVID-19 Pandemic requires strategic, solid controls. In this passage, under the COVID-19 background, we summarize the factors that cause increasing production and usage of plastic, highlight the effects of producing and using a large amount of plastic, and propose some ways to deaden the environmental problems caused by the mass production of plastic products under the epidemic. Several factors are pushing the production and usage of plastics, including changes in people's behavior, demand for protective equipment, and laws and regulations. These factors drive the production of plastic substances, bringing with them a series of serious environmental, economic, and human health problems. Thus, we propose three ways, including the government leadership, social participation, and individual responsibility, to de-escalate the detriment caused by the plastic matter.